“Makrifat Sasak” Memahami Konsep Mengenal Diri dalam Simbol Budaya Sasak - Sirajun Nasihin (LP2M IAIN Palangka Raya, 2018)
This study is aimed at describing the philosophical meaning of advice of Sasak parents from the perspective of Sufism. The advice reads: mbe mbe laine lampaq dendeq lupaq jauq gaman mane manen besi polka”. This study is a literature study attempting to investigate the concept of Sasak Makrifat theoretically and philosophically. The researcher believes that the advice besides having an outward meaning also holds a very depth spiritual meaning in which gaman is not only a weapon as is generally, but also, gaman is another term for religion. After describing the meaning behind the term of the gaman, it can be concluded that the meaning of the advice is: